1998
DOI: 10.3181/00379727-217-44222
|View full text |Cite
|
Sign up to set email alerts
|

Hypophyseal-Portal Concentrations of Growth Hormone-Releasing Factor and Somatostatin in Conscious Pigs: Relationship to Production of Spontaneous Growth Hormone Pulses

Abstract: A method of collecting hypophyseal portal blood (HPB) in conscious pigs was used to show the relationship between GRF and somatostatin (SRIF) concentration and peripheral GH response. Six male castrate pigs (approximately 63 kg body weight) had HPB and jugular blood collected individually for an average of 175 min each. Twenty-seven spontaneous GH pulses were detected in the 1050 min of total HPB collection. Of the associations examined, the only significant finding was that GH pulse maxima occurred nonrandoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
0
10
1
1
Order By: Relevance
“…Furthermore, it was suggested that restricted feeding affected the hypothalamic control of GH secretion in sheep (Thomas et al, 1991). Drisko et al have suggested that SS has a closer relationship with GH pulses than GHRH, as determined by portal blood sampling in castrated male pigs (Drisko et al, 1998). In our study performed in intact male calves, a close relationship among these three parameters was not observed.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Furthermore, it was suggested that restricted feeding affected the hypothalamic control of GH secretion in sheep (Thomas et al, 1991). Drisko et al have suggested that SS has a closer relationship with GH pulses than GHRH, as determined by portal blood sampling in castrated male pigs (Drisko et al, 1998). In our study performed in intact male calves, a close relationship among these three parameters was not observed.…”
Section: Discussioncontrasting
confidence: 60%
“…Pulsatile GH secretion has been observed in most species studied, including rats (Tannenbaum and Martin, 1976), humans (Finkelstein et al, 1972), monkeys (Woller et al, 2002), pigs (Drisko et al, 1998), goats (Mogi et al, 2002), sheep (Frohman set al, 1990) and cattle (Breier et al, 1986;Lee et al, 1991;Plouzek and Trenkle, 1991). GH pulses clearly occur regularly at approximately 3.3 h intervals in male rats (Tannenbaum and Martin, 1976).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This model is supported by studies using immunoneutralization of GHRH and somatostatin (65, 80), GHRH, or somatostatin antagonists (5,33,34,73), as well as direct pituitary portal sampling in experimental animals (18,20,55,66). A reciprocal relationship between GHRH and somatostatin, where GHRH pulses coincide with somatostatin troughs, has been reported in rats (37,55,65), but this pattern is less clear in sheep or pigs, where more complex relationships between oscillations in GHRH, somatostatin, and GH prevail (8,15,20,66). Thus important species as well as sex differences exist in the regulation of GH secretion.…”
mentioning
confidence: 51%
“…Greater hypothalamic somatostatin mRNA expression at 3.5 mo of age compared to the other ages supports the idea of an age-related decline in GH secretion related to increased somatostatin secretion. Furthermore, Drisko et al [21] reported a temporal relationship between hypophyseal-portal blood concentration of somatostatin and generation of serum GH pulses in the pig.…”
Section: Discussionmentioning
confidence: 97%